The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/srep03981
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of Baihui (GV20)-based scalp acupuncture in experimental ischemic stroke

Abstract: Acupuncture for stroke has been used in China for over 2,000 years and nowadays is increasingly practiced elsewhere in the world. However, previous studies had conflicting findings on the results of acupuncture. Here, we conducted a systematic review and meta-analysis to assess the current evidence for the effect of Baihui (GV20)-based scalp acupuncture in animal models of focal cerebral ischemia. Six databases from the inception of each database up to June 2013 were electronically searched. Primary outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 50 publications
1
73
0
1
Order By: Relevance
“…The whole process and methods of this meta-analysis were performed according to our previous published paper35.…”
Section: Methodsmentioning
confidence: 99%
“…The whole process and methods of this meta-analysis were performed according to our previous published paper35.…”
Section: Methodsmentioning
confidence: 99%
“…Electroacupuncture (EA), or engrafted electric stimulation, is accepted as a common complementary therapy for stroke and post-stroke rehabilitation7. Although the efficacy of EA in stroke treatment remains controversial, most available evidence suggests that acupuncture promotes the recovery of neurological function and thus improves quality of life after stroke891011. However, the underlying mechanism of the enhancement of neurofunctional recovery by EA after ischemic stroke remains to be elucidated.…”
mentioning
confidence: 99%
“…A meta-analysis concluded that acupuncture stimulation at the point GV20 reduced the area of infarction in animal models of experimental ischemic stroke, improved neurological function scores, and showed a potential neuroprotective effect [18]. A recent study reported that acupuncture stimulation at the point HT7 in a rat model with cognitive deficit reduced damage to cholinergic neurons and showed a neuroprotective effect by regulating Creb and Bdnf gene expressions [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported that acupuncture stimulation at the acupuncture points GV20 [18] and HT7 [19] in animal models showed potential neuroprotective effects and improvement of cognitive deficits. However, the molecular mechanisms associated with LA's neuroprotective effects and alleviation of cognitive deficits after brain ischemia are unclear.…”
Section: Introductionmentioning
confidence: 99%